2010
DOI: 10.1007/s00438-010-0550-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a fission yeast mutant that is sensitive to valproic acid and defective in the gene encoding Ric1, a putative component of Ypt/Rab-specific GEF for Ryh1 GTPase

Abstract: Valproic acid (VPA) causes various therapeutic and biological effects, but the exact mechanisms underlying these effects, however, remain elusive. To gain insights into the molecular mechanisms of VPA action, we performed in fission yeast a genetic screen for mutants that show VPA hypersensitivity and have identified several membrane-trafficking mutants including vas1-1/vps45 and vas2-1/aps1. Here, we describe the isolation and characterization of vas3-1/ric1-v3, a mutant allele of the ric1 (+) gene encoding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…Ryh1 regulates the intra-Golgi trafficking and is involved in recycling from endosome to the Golgi, as well as in trafficking events from the Golgi to the plasma membrane232547. Here we obtained strong evidence supporting that Ryh1 controls the activity of the CIP through an additional mechanism independent of its role as an upstream regulator of TORC2 signaling (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Ryh1 regulates the intra-Golgi trafficking and is involved in recycling from endosome to the Golgi, as well as in trafficking events from the Golgi to the plasma membrane232547. Here we obtained strong evidence supporting that Ryh1 controls the activity of the CIP through an additional mechanism independent of its role as an upstream regulator of TORC2 signaling (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…GTP-bound Ryh1 associates with TORC2 to induce phosphorylation and activation of Gad8 during growth, and its GTPase activity is strongly reduced under glucose starvation22. Ryh1 localizes mainly to the Golgi apparatus, and also regulates membrane trafficking from endosomes to Golgi, ER, and plasma membrane232425.…”
mentioning
confidence: 99%
“…First, we assessed the growth of Δ ryh1 and Δ ric1 cell, which showed FK506 sensitivity in our previous study [31], on YES plus FK506 or YPDA plus FK506 plates. The results showed that Δ ryh1 and Δ ric1 cells completely failed to grow on YPDA plus FK506 plates, whereas the cells partially grew on YES plus FK506 plates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Both Ryh1p and Ypt3p localize to the Golgi apparatus and endosome, where they regulate protein secretion and the recycling of the exocytic SNARE from endosomes to Golgi apparatus (49). The GEF for Ryh1p is presumed to be Ric1p, a component of the Ric1p/Rgp1p complex, which in budding yeast serves as a GEF for Ypt6p (50, 51). Although the GEF activity of Ric1p toward Ryh1p is unproven and it is unclear if Ric1p is an effector of Ypt3p, one could speculate that Ryh1p and Ypt3p form a Rab GEF cascade through the Ric1p/Rgp1p complex.…”
Section: Guanine Nucleotide Exchange Factor Cascadesmentioning
confidence: 99%